2008
DOI: 10.1088/0964-1726/17/2/025017
|View full text |Cite
|
Sign up to set email alerts
|

A piezoelectric fibre composite based energy harvesting device for potential wearable applications

Abstract: Rapid technological advances in nanotechnology, microelectronic sensors and systems are becoming increasingly miniaturized to the point where embedded wearable applications are beginning to emerge. A restriction to the widespread application of these microsystems is the power supply of relatively sizable dimensions, weight, and limited lifespan. Emerging micropower sources exploit self-powered generators utilizing the intrinsic energy conversion characteristics of smart materials. 'Energy harvesting' describes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
101
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 180 publications
(104 citation statements)
references
References 16 publications
2
101
0
1
Order By: Relevance
“…Swallow et al [11] reported that in piezoelectric fibre composites (PFC) the distance between the fibres also affected the voltage generation and there is an optimum distance to diameter ratio between the fibres that leads to the highest voltage generation otherwise there will be arcing losses. Poled and unpoled PVDF fibres were investigated under SEM at various magnifications and on various locations of the fibres.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Swallow et al [11] reported that in piezoelectric fibre composites (PFC) the distance between the fibres also affected the voltage generation and there is an optimum distance to diameter ratio between the fibres that leads to the highest voltage generation otherwise there will be arcing losses. Poled and unpoled PVDF fibres were investigated under SEM at various magnifications and on various locations of the fibres.…”
Section: Resultsmentioning
confidence: 99%
“…Li et al [2] and Vatansever et al [9] demonstrated that piezoelectric PVDF can be used to generate a continuous power of the order of 100 µW using wind energy at moderate wind speeds. Most of the earlier research reported that ceramic based piezoelectric structures generated higher voltage than the piezoelectric PVDF structures [10] [11]. Vatansever et al [9] have recently demonstrated that under certain conditions such as generation of energy from the wind and rain, piezoelectric PVDF generated higher voltage and power compared to ceramic based PZT and Piezoelectric Fibre Composite (PFC) structures.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that 45.6mW of power could be generated from a complete backpack with two piezoelectric straps with an efficiency of more than 13%. Swallow et al [39] developed a micropower generator using micro composite based piezoelectric materials for energy reclamation in glove structures. They developed fibre composite structures by using different fibre diameters embedded between two copper electrodes and both the effect of fibre diameter and the materials thickness were investigated.…”
Section: History and Recent Developments On Piezoelectric Energy Harvmentioning
confidence: 99%
“…Theoretically, any kind of vibration source can be transformed into electric power [8]. There are three basic techniques for this kind of conversion: piezoelectric transducers-energy is induced by the deformation of piezoelectric materials, like PZT ceramics, PVDF films and piezoelectric composite fibers [9]; spring-mass electromagnetic transducers-energy is generated between a moving magnet and a coil based on Faraday's law [10][11][12]; and electrostatic transducers-energy is generated by charged vibrating capacitor electrodes [13,14].…”
Section: Introductionmentioning
confidence: 99%